Effect of Telenursing on Attachment and Stress in Mothers of Preterm Infants - Zahra Alsadat Jafarzadeh; Jahangir Maghsoudi; Behzad Barekatain; Maryam Marofi (Mashhad University of Medical Sciences, 2019)
Background: The necessity of professional nursing support to increase the role of families in neonatal care and their empowerment has been a subject of growing attention. The aim of this study was to determine the effect of telenursing on attachment and stress in the mothers of premature infants. Methods: In this clinical trial, 50 mothers with premature infants who were admitted to neonatal intensive care unit (NICU) at Shahid Beheshti Hospital in Isfahan with a gestational age of more than 33 weeks were selected by convenience sampling method. They were randomly assigned to two groups of intervention (n=25) and control (n=25). The intervention group received an educational program designed through telephone and counseling center for the mothers of premature infants that started one week after the admission and continued one week after discharge. However, the control group only received the usual care provided in the NICU. One week after the admission of the infant, Maternal Postnatal Attachment (MPA) and Parent Stressor Scale: Neonatal Intensive Care Unit (PSS-NICU) questionnaires were completed. The PSS-NICU questionnaire and MPA questionnaire were completed at the time of discharge and one week after the discharge by the participants, respectively. Results: The average increase in total attachment scores one week after discharge was significantly higher in the intervention group, compared to that of the control group (P